Reactivation of Dormant Lenticels by Exogenous Application of STIK and GA3 - Badola, Hemant K.; Badoni, Arun K.; Sharma, S. P. (Indian Forester, 1990)
Tbe cuttings of Holoptelea integrifolia and Pyrus pashia trees receiving STIK as well as GA3 at 0.1,0.2,0.5, 1.0 and 2.0 mgmt-1 levels showed that the stimulalion of lenlicels is more or less paralleled in the two taxa. The higher concentrations of STIK proved more effective in inducing new lenticels, whereas GA3 showed a pronounced influence at lower concentrations.